High Capacity Image Steganography System based on Multi-layer Security and LSB Exchanging Method - Hameed R.S.; Mokri S.S.; Taha M.S.; Taher M.M. (Science and Information Organization, 2023)
Data transfer; Economic and social effects; Image processing; Steganography; High capacity; High capacity component; High-capacity; High-capacity images; Image steganography; Information hiding; Least significant bits; Multi-layer security; Multi-layers; Pay load capacity; Cryptography